2023
DOI: 10.3390/agronomy13061581
|View full text |Cite
|
Sign up to set email alerts
|

The Effective Combination of Humic Acid Phosphate Fertilizer Regulating the Form Transformation of Phosphorus and the Chemical and Microbial Mechanism of Its Phosphorus Availability

Abstract: In the process of phosphate fertilizer production, adding humic acid to produce humic-acid-value-added phosphate fertilizer can improve fertilizer efficiency and promote crop growth. Although studies have primarily focused on investigating the impact of humic acid’s structure and function on phosphorus availability in humic-acid-added phosphate fertilizers, there is limited research on the regulatory effects of phosphorus fertilizer structure and the synergistic mechanisms involving microorganisms. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Research has shown that humic acid enhances the dissolution of K + by acidifying the soil and increases the availability of nutrients 108 . Also, humic acid with its pseudo-cytokinin role has a positive effect on increasing K + absorption 109 . The findings of the present research showed that the application of humic acid plays an effective role in improving the absorption of elements such as Ca 2+ and K + while reducing the absorption of Na + and Cl − in cucumber leaf and root under salt stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that humic acid enhances the dissolution of K + by acidifying the soil and increases the availability of nutrients 108 . Also, humic acid with its pseudo-cytokinin role has a positive effect on increasing K + absorption 109 . The findings of the present research showed that the application of humic acid plays an effective role in improving the absorption of elements such as Ca 2+ and K + while reducing the absorption of Na + and Cl − in cucumber leaf and root under salt stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, both total phosphate and sulfate are still needed to meet other needs. Total phosphate is needed to complete the nutrients in fertilizer [8], as well as sulfate [9]. Nanofiltration membrane technology in various studies has proven the total removal of phosphate and sulfate in industrial wastewater.…”
Section: Introductionmentioning
confidence: 99%